Optimization of mechanical structures using interval analysis - Pownuk, Andrzej (Computer Assisted Methods in Engineering and Science, 2000)
The problem of optimal design consists in finding the optimum parameters according to a specified optimality criterion. Existing optimization methods [25, 27] usually are not reliable or cannot use the nondifferentiable, not continuous objective functions or constraints. An interval global optimization method is very stable and robust, universally applicable and fully reliable. The interval algorithm guarantees that all stationary global solutions have been found. In this paper the algorithm is applied to optimization of mechanical systems, calculation of extreme values of mechanical quantities and to optimization of structures with uncertain parameters.